Reproductive biology of the spotback skate Atlantoraja castelnaui in the south-west Atlantic Ocean - Colonello, J. C. (2012)
This study provides information on the reproduction of spotback skate Atlantoraja castelnaui. A total of 232 individuals (119 females and 113 males) were obtained from surveys carried out between 2003 and 2006, from the south-west Atlantic Ocean, between 34 and 42° S and <50 m deep; another 514 specimens (241 females and 273 males) were obtained between 2005 and 2007 from commercial fishery operations carried out in the same area and landings in the port of Mar del Plata, Argentina. Males ranged from 185 to 1250 mm total length (L T) and females from 243 to 1368 mm L T. Length at maturity was estimated to be 980 mm for males and 1089 mm L T for females. Lack of variation of testis mass together with the continuous production of mature spermatocyst and spermatozoa in deferent ducts suggested that males can reproduce throughout the year. Females reproduced year-round with peaks of reproductive activity an integral part of a continuous cycle. This conclusion is corroborated by the seasonal variation of ovaries, oviducal gland and the occurrence of females with eggs in the uterus throughout the year. Results from this study indicate that A. castelnaui is very susceptible to fishery pressure.